A formação do tradutor e do intérprete surdo de língua de sinais no ensino superior: questões curriculares - Sousa, Jucemara Aguiar (2021)
This paper conduct to discuss the academic education of deaf people who studies Libras translation and interpreting courses in university education. It was carried out a bibliographic survey of the Pedagogical Political Projects (PPCs) of the bachelor's degree in Letras Libras courses and in Translation and Interpretating in Brazilian Sign Language - Libras and Portuguese Language offered by nine public universities and subsequently, a curriculum analysis of the courses was accomplished. The research aimed to know if these courses are prepared, in a curricular point of view, to receive a deaf student who has different specificities from hearing students and also wants to become a translator and interpreter. Through analyzes realized in the curricular projects, we found challenges that permeate the possibility of the deaf interpreters’ qualification, the difficulties founded in lessons that are sometimes taught in Portuguese. The curricular reality evidenced during this research demonstrate that, the connexion between theory and practice regarding the education of deaf translators and interpreters, is very distant, once bachelor's degrees in Libras translation and interpretation offered by the analyzed institutions were not designed to contemplating the education of deaf professionals. The research reveals gaps and the need to think about deaf person as a possible student of the courses, since the specific education as a translator and interpreter for this group is still very recent.